The Development of Vocational Career Guidance Module in Food Serving Process to Improve Career Decision Making Ability of Vocational High School Students - Istianingsih, Yen Ruri; Khumaedi, Muhammad; Sutopo, Yeri (Universitas Negeri Semarang, 2021)
Vocational high school is an educational institution that aimed to create graduates who have good quality and competence in a certain field. The students need to be provided career insight from the beginning of entering the school. The vocational guidance module is crucial for the students. The research study consisted of 1) How is the development of vocational career guidance in the food serving process improve the career decision-making ability of vocational high school students? 2) What is the feasibility of the module? 3) how is the practicality of the module? 4) how is the effectiveness of the module?. This research applied Research and Development method (RD). The present study used the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. The research analysis unit was a vocational career guidance module on the food serving process. This research used some instruments to gain the data: 1) assessment sheets of vocational career guidance modules; 2) questionnaires on the practicality of modules, and (3) questionnaires to measure student career decision making. The validity of the assessment sheet is obtained from the calculation of the CVR and its reliability using the ICC formula. The questionnaire validity applied point biserial, while the reliability questionnaire used KR20 formulas. The result of the feasibility test, practicality test, and effectivity test based on media and material experts of the developed module was feasible. Furthermore, the user product like teachers and students stated that the module was very practical, quite effective, and significant to improve the career decision making of vocational high school (SMK) Culinary Art.